2017
DOI: 10.1002/jcph.956
|View full text |Cite
|
Sign up to set email alerts
|

Notable Drug–Drug Interaction Between Etizolam and Itraconazole in Poor Metabolizers of Cytochrome P450 2C19

Abstract: In this study, impact of a polymorphism of CYP2C19 on drug-drug interaction (DDI) was examined for etizolam. The effect of itraconazole (a strong CYP3A inhibitor) on the pharmacokinetics of etizolam (a substrate of CYP2C19 and CYP3A) was assessed in both extensive metabolizers (EMs) and poor metabolizers (PMs) of CYP2C19. Sixteen participants (8 EMs and 8 PMs) received a single oral dose of etizolam (0.25 mg) on day 1. The participants ingested itraconazole (200 mg twice a day) on days 2-5. On day 5, participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Carbamazepine (a CYP3A4 inducer) increases etizolam metabolism , and itraconazole (a CYP3A4 inhibitor) inhibits it , indicating that interactions may occur with these drugs. CYP2C19 polymorphism can place poor metabolisers at higher risk of a drug–drug interaction . CYP2C19 deficiency may lead to side effects or toxicity with etizolam .…”
Section: Resultsmentioning
confidence: 99%
“…Carbamazepine (a CYP3A4 inducer) increases etizolam metabolism , and itraconazole (a CYP3A4 inhibitor) inhibits it , indicating that interactions may occur with these drugs. CYP2C19 polymorphism can place poor metabolisers at higher risk of a drug–drug interaction . CYP2C19 deficiency may lead to side effects or toxicity with etizolam .…”
Section: Resultsmentioning
confidence: 99%
“…21) On the other hand, itraconazole, ketoconazole, erythromycin, and clarithromycin each inhibit the metabolism of imidafenacin by decreasing the metabolic activity of CYP3A4. 22) Although CYP3A4 could reasonably enable DDIs owing to its wide substrate cavity, a recent study showed that etizolam metabolism by another isoform, CYP2C19, is affected by co-administration of itraconazole. 23) CYP2C19 is one of the major CYP isoforms 17) and is responsible for metabolism of at least 10% of commonly used clinical drugs.…”
Section: Highlighted Paper Selected By Editor-in-chiefmentioning
confidence: 99%
“…Peimine was previously reported to exert inhibitory effects on the activity of various cytochrome P450 enzymes (CYP450s), including CYP3A4, 2E1 and 2D6, which are key mediators during the pharmacokinetics of various xenobiotics, including paeoniflorin (Li et al 2020). Previously, the inhibition or induction of CYP450s was considered as the main cause of the adverse drug-drug interaction between different drugs, which has been widely reported (Geffrey et al 2015;Yamamoto et al 2017;Nishihara et al 2019). It is speculated that the co-administration of peimine and paeoniflorin would induce drug-drug interaction, which might lead to failure of treatment or even drug toxicity.…”
Section: Introductionmentioning
confidence: 99%